ANALISIS PREDIKSI FINANCIAL DISTRESS SERTA PENGARUHNYA TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia Tahun 2009–2013) - Bastomi, Mohamad; Meldona, Meldona (IQTISHODUNA, 2015)
All of investors value that financial distress conditions and the proportion of financial capitalstructure have effect to become fluctuation of stocks price. Therefore, the aim of this research is to know theeffects of financial distress to the stocks’ price either direct or indirect through financial capital structure. Thisresearch uses descriptive quantitative approach by using sector of service listed in BEI year 2009–2013 as theobject. The sampling method used is purposive sampling. There are 23 companies that have categorized assample. The method that used to predict financial distress is z-score Altman method, whereas to analyst thehypothesis is used path analysis through SPSS TEST by consideration of test classic assumption. Based onthe result the research shows that financial distress gives negative impact to the stocks’ price. Financialdistress caused by capital loss so decrease work of money that effect to the decrease stocks price. It might becaused of using financial structure proportion doesn’t cause business risk that will emerge financial Distressuntil it doesn’t moving stocks price. From Altman z-score prediction shows from 23 companies 10 of it (APOL,BIPP BLTA, BTEL, FMII, HITS, IATA, LIMAS, RIMO, and TKGA) include on financial distress category.Meanwhile, 5 companies (BHIT, BKDP BMSR, OKAS, and ZBRA) include on gray area. Furthermore 8 companies(ASIA, BNBR, CENT, ELTY, LCGP, META, TRIL, and TRUB) include in save condition.